PREDICTION OF ATMOSPHERE POLLUTION IN CASE OF EMISSIONS FROM MAIN MINE FANS - Biliaiev, M. M.; Bondarenko, I. O.; Rusakova, T. I.; Shynkarenko, V. I.; Gabrinet, V. A. (Science and Transport Progress, 2019)
Purpose. Emissions from mine ventilation system can create intensive atmosphere air pollution. As a rule, a huge amount of dust from mine fan enters atmosphere low layers. An important task is the development of methods to assess levels of the atmosphere pollution near mines and settlements. To solve this problem it is important to have physically proved mathematical models. Nowadays to predict the atmosphere pollution near settlements which are effected by mine fan the empirical model OND–86 is used. This model does not take into account many important physical factors. So, the purpose of this study is the development of quick computing mathematical model to predict the atmosphere pollution in case of dust emissions from mine fan. Methodology. To predict levels of the atmosphere pollution in case of mine fan work 3D equation of dust convective – diffusive flow was used. This equation takes into account gravity fallout, wind velocity, atmosphere turbulent diffusion, location of dust emission source. To sole modeling equation the implicit difference scheme of splitting was used. Findings. Developed mathematical model allows quick prediction of the level of atmosphere pollution in case of dust emissions from mine ventilation fan. The models allow to obtain zones of contamination near settlements which are situated in vicinity of mine. Originality. The developed mathematical model takes into account a number of physical factors, which at the present time are not considered on the days when prediction of the atmosphere pollution in settlements near mine is carried out. Practical value. On the basis of the developed mathematical model program code was created. This code can be used for evaluation of atmosphere pollution in settlements which are effected mine fan emissions.